2016
DOI: 10.2147/copd.s105206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for postoperative pulmonary complications after lung cancer surgery in patients with early-stage COPD

Abstract: PurposeThis study aimed to investigate whether the prevalence of postoperative pulmonary complications (PPCs) in patients with non-small-cell lung cancer (NSCLC) is even higher in the early stages of COPD than in such patients with normal lung function and to verify the usefulness of symptom- or quality of life (QoL)-based scores in predicting risk for PPCs.Patients and methodsPatients undergoing pulmonary resection for NSCLC between July 2012 and October 2014 were prospectively enrolled. Preoperative measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 44 publications
(27 reference statements)
3
64
1
7
Order By: Relevance
“…Previously published studies have shown COPD to be a well-known risk factor for postoperative pulmonary complications. 28,29 Whereas PR improves the functional parameters responsible for inoperability, 22 the selection criteria for enrolling patients in PR are still controversial. A recent study demonstrated that, even in patients with early-stage COPD, the prevalence of postoperative pulmonary complications was higher than in NSCLC patients with normal spirometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published studies have shown COPD to be a well-known risk factor for postoperative pulmonary complications. 28,29 Whereas PR improves the functional parameters responsible for inoperability, 22 the selection criteria for enrolling patients in PR are still controversial. A recent study demonstrated that, even in patients with early-stage COPD, the prevalence of postoperative pulmonary complications was higher than in NSCLC patients with normal spirometry.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that, even in patients with early-stage COPD, the prevalence of postoperative pulmonary complications was higher than in NSCLC patients with normal spirometry. 29 In the present retrospective review, the non-PR group included stage I COPD. Our finding that PR reduced postoperative pulmonary complications may indicate that PR should be performed even at stage I COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the frequencies of all postoperative pulmonary complications (PPCs), including pneumonia (10.1%-16.2% in COPD patients following lung cancer surgery) [7779], atelectasis (3.5%-15.4%) [79, 80], empyema (2.2%-8.3%) [78], and persistent air leak (12%-16.2%) [77, 81], were often higher in COPD patients. Therefore, an accurate risk assessment in patients with lung cancer coexisting with COPD is critically important, in order to optimize treatment for these patients.…”
Section: Treatment For Lung Cancer With Copdmentioning
confidence: 99%
“…Most studies on pulmonary resections for NSCLC -and especially lobectomy -have focused more on short-term outcome than on long-term survival [12,13]. These studies have usually been based on single tertiary-care centers, with the risk of selection bias.…”
Section: Introductionmentioning
confidence: 99%